Pengembangan Buku Ajar Cara Cepat Membaca Aksara Jawa dengan Metode Al-Barqy di Tingkat Sekolah Menengah Pertama - Masruchi Adyningsih; Retno Danu Rusmawati; Nunung Nurjati (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2022)
AbstractLearning to read Javanese script is an effort to preserve Javanese letters and Javanese culture. While in learning so far, reading Javanese script is mastered by students only during reading and writing lessons. They will quickly forget the characters they have learned once the material is finished. This kind of condition is certainly not good in mastering a subject matter. The approach model used in this research is the Research and Development (R&D) approach. Development research is research that is used to produce certain products, to test the effectiveness of these products. Research is used to produce certain products that are needs analysis and test the effectiveness of these products to function in the wider community, thus research is needed to test the quality of these products. To achieve this, research and development has a gradual nature in producing its products. Research and development (Research and Development) is a research method used to produce certain products and test the effectiveness of these products. The product development of textbooks on how to quickly read Javanese script with the Al-Barqy method for class VII students at State Junior High School 1 Ngoro Mojokerto has been developed and has been tested for validity and the product can be used in the implementation of product design for developing textbooks on how to quickly read Javanese script with the Al-Javanese method. Barqy is a seventh grader at the State Junior High School 1 Ngoro Mojokerto. Due to time and cost limitations in carrying out this research, the researchers did not carry out this research within the scope of field trials. Field trials involved schools other than small group trials, limited trials and large group trials. Field group trials involving schools within the school environment in sub-districts, districts, cities or provinces require very large funds.Keywords: Reading Skills, Javanese Script, Al Barqy Method